Program Literasi Pajak Penghasilan Pasal 21 (Pph 21) Untuk Guru Dan Tenaga Kependidikan Dalam Upaya Meningkatkan Kepatuhan Dan Akuntabilitas Pajak Di Sektor Pendidikan - Mega Arum; Hindayani, Novia (JPM: Jurnal Pengabdian Masyarakat, 2025)
The Income Tax (PPh 21) literacy program for teachers and educational staff aims to enhance understanding, compliance, and tax accountability in the education sector. Income Tax (PPh 21) is a tax levied on income in the form of salaries, wages, honoraria, allowances, and other payments related to work, services, or activities carried out by individuals. Teachers and educational staff, as income earners, are required to understand their tax obligations in order to fulfill them accurately and in accordance with applicable regulations. Through this program, teachers and educational staff are educated on the calculation, withholding, and reporting of PPh 21. This literacy initiative also aims to raise awareness of the importance of paying taxes to support national development. In addition, the program emphasizes the importance of accountability in financial administration, particularly in the education sector, so that educators can actively contribute to maintaining fiscal transparency. The research method used in this study is descriptive qualitative research with a literature review approach. This study aims toidentify and analyze the impact of the literacy program on improving the understanding and compliance of teachers and educational staff regarding tax obligations. Data collection was carried out through literature studies and documentation, which were then analyzed thematically. The results of this program are expected to improve PPh 21 compliance among teachers and educational staff, as well as encourage the creation of better financial management systems in educational institutions. Increased awareness of PPh 21 will significantly contribute to state revenue, which in turn can improve the quality of education in Indonesia through better budget allocation.